PEMANFAATAN USB KONVERTER KE RS-485DAN MIKROKONTROLER AVR ATTINY2313 PADA SISTEM POLLING - Masarrang, Maryantho (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2013)
Almost people in Indonesia ever seen quiz who wants to be millionaire. That quiz is sometimes using a polling method to get the right answer. Audience at studio must help a quiz’s participant by using keypad to get a right answer. Audience must push the button of   keypad where there is choice of answers. After that the answer will be display in a bar graph of percent. This called electronic polling system. With the aim of the research is to design and build a polling system with 6 slave-based serial RS-485, USB and microcontroller RISC and design and build a control system based serial RS-485, USB and microcontroller RISC efficient. The method used in this research is to study the reference, namely collecting materials that can be used as a reference, observation and study references required, inventory problems and needs in the design and manufacture, design and manufacture of hardware, software design and manufacturing, and perform testing. RS-485 is standard for communication with very long cable. This standard can use cable almost 1,2 Km long. RS-485 is very unique, this standard using master slave method. So only the master can control slave. Slave is using a microcontroller to manage data. AVR ATtiny2313 is a good microcontroller for slave. This is microcontroller very small and very fast. Base from design, implementation and test result indication implement of  RS-485 at polling system can be handle of case distance between master and slave. Beside that not only one slave can be connected to master. Keyword : polling system, USB, RS-485, AVRATtiny2313